Influência da maturidade de Business Intelligence & Analytics sobre usos dos sistemas de medição de desempenho: estudos de caso - Xavier, José Eduardo Mendonça (2018)
Given the potential that the development of Business Intelligence and Analytics (BI&A) can bring to organizations, in particular to the uses of the Performance Measurement System (PMS), and considering the shortage of works of this nature, this thesis had as main purpose to identify how the development of BI&A capabilities influences the uses of the PMS in organizations. A multiple case study was used as an empirical research object in eight small, medium and large organizations located in the states of São Paulo, Espírito Santo and Minas Gerais. Public and private organizations were studied, encompassing the activities of telecommunications services, call center, e-commerce, cosmetics industry and retail, justice, energy services and water and sewage services. The analysis was performed using interviews with key actors, document analysis and the application of a maturity model of BI&A. The results indicate that as organizations grow in BI&A maturity there are benefits over the analyzed uses of Performance Measurement System: control, improvement and planning. Throughout the development of maturity, the increasing capabilities of BI&A such as, information quality, culture of information use and functionalities (for example, visualization, self-service BI and predictive techniques), leverage the uses of PMS. There are benefits to the uses of PMS in the studied organizations, mainly in the operational management level, in aspects such as performance indicators monitoring, coverage of the use of indicators, business understanding, identification of deviations and problems, capacity to respond to changes and resources management.